Investigating the Influence of Rigden Void of Fillers on the Moisture Damage of Asphalt Mixtures - Jirat Wuttisombatjaroen; Nithinan Hemnithi; Preeda Chaturabong (Civil Engineering Journal, 2023)
Moisture damage and bond loss are major factors in pavement degradation, often stemming from excessive moisture accumulation due to weather events. Water infiltrates the gap between asphalt binder and aggregate, weakening the asphalt bond. Rigden Void (RV) has emerged as a crucial parameter in assessing the susceptibility of asphalt mastic-aggregate systems to moisture-induced damage. However, numerous waste natural fillers have been researched as potential aggregate filler replacements, yet their role in moisture damage remains unexplored. Therefore, this study aimed to understand how different fillers, including waste natural materials like coconut peat and bagasse, affect asphalt mixture performance and moisture damage. Results showed that Rigden Voids were positively correlated with pore size and negatively correlated with surface area. Larger pores contributed to higher Rigden Voids, while greater surface areas led to lower values. Limestone had the highest Rigden Void percentage due to its larger pore size and lower surface area. The research also explored contact parameters between fillers and asphalt, revealing varying interactions based on filler and asphalt types. Moisture damage testing demonstrated that all mixtures, both dense and porous, displayed good resistance to moisture damage. The correlation analysis between Rigden Voids and moisture damage revealed varying degrees of influence, dependent on asphalt type and aggregate gradation. Doi: 10.28991/CEJ-2023-09-12-014 Full Text: PDF